Evaluation of Nickel Catalysts Supported in Dry Methane Reform Aiming at Hydrogen Production/Case of Supports: SiO2, La2O3 MCM-41, and Al2O3 - da Silva, Paulo Roberto Nagipe; Zanoteli, Karine (Orbital: The Electronic Journal of Chemistry, 2020)
The importance of biogas was evidenced by the dry reforming reaction using a nickel catalyst supported: Al2O3, SiO2, MCM 41 and La2O3. The catalysts were characterized using electron scanning microscopy, Chemisorption, BET, X- Ray analysis.  The reaction was conducted in a quartz reactor, atmospheric pressure and at temperatures of 500, 600 and 700 oC. The catalysts showed different conversions in syngas with the change of temperature, and H2/CO ratio variable. The nickel catalyst supported on alumina showed the most activity in the three reaction temperatures. The conversion of supported nickel catalysts, in the examined temperatures, decreased in the following order: Ni/Al2O3 ˃ Ni/La2O3 ˃ NiSi/O2 ˃ Ni/MCM41. The Ni/Al2O3 and Ni/MCM-41 catalysts showed H2/CO greater than one at all temperatures.DOI: http://dx.doi.org/10.17807/orbital.v12i3.1495